1990
DOI: 10.1126/science.250.4988.1705
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Desert-Grassland Transition by a Keystone Rodent Guild

Abstract: Twelve years after three species of kangaroo rats (Dipodomys spp.) were removed from plots of Chihuahuan Desert shrub habitat, density of tall perennial and annual grasses had increased approximately threefold and rodent species typical of arid grassland had colonized. These were just the most recent and drmatic in a series of changes in plants and animals caused by experimental exclusion of Dipodomys. In this ecosystem kangaroo rats are a keystone guild: through seed predation and soil disturbance they have m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
497
6
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 565 publications
(539 citation statements)
references
References 18 publications
27
497
6
9
Order By: Relevance
“…Further, annuals average only about 6% of total plant cover . Some cases where non-social small mammals have been important in altering plant communities have been in those with a substantial component of annuals (Brown and Heske, 1990), or where outbreaks of small mammals were noted coincident with their impact (Noy-Meir, 1988), neither of which occurred at this site. Although numbers of small mammals can fluctuate widely, those for lagomorphs and the two most abundant species of rodents did not show any unusual peaks from 1994-2001, except for a peak in deer mice in 1996 followed by a crash the next year (Stapp et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, annuals average only about 6% of total plant cover . Some cases where non-social small mammals have been important in altering plant communities have been in those with a substantial component of annuals (Brown and Heske, 1990), or where outbreaks of small mammals were noted coincident with their impact (Noy-Meir, 1988), neither of which occurred at this site. Although numbers of small mammals can fluctuate widely, those for lagomorphs and the two most abundant species of rodents did not show any unusual peaks from 1994-2001, except for a peak in deer mice in 1996 followed by a crash the next year (Stapp et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Much less is known about the impacts of small specialist herbivores, although again the effects can vary from small to very large (Brown and Heske, 1990;Hulme, 1994;Edwards and Crawley, 1999;Keesing, 2000;Maron and Simms, 2001;Bakker et al, 2006). In some of the cases above, the effects of the small herbivores are due to consumption of seed and seedlings in plant communities with a substantial annual component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the per capita probability of seedling mortality is nonrandom because the probability of death is not the same for all individuals in a local community -it is dependent to some degree on species identity. In plant communities in which generation times are relatively short, experiments have demonstrated that nonrandom mortality through these early transitions can be sufficiently strong to affect the species composition of mature plants (26)(27)(28)(29). Such demonstrations are impossible in studies of a few decades or less in duration when generation times are long and even juveniles live for several decades or centuries, such as in many tropical forests.…”
mentioning
confidence: 98%
“…Benthlc ecologists must expand their efforts to encompass longer and larger scales (Brown 1995). Some work of this nature has been done (e.g.…”
Section: Effects Of Human Exploitationmentioning
confidence: 99%